Immune responses to tumour antigens: implications for antigen specific immunotherapy of cancer. Issue 9 (1st September 2001) - Jäger, D; Jäger, E; Knuth, A
Abstract : Tumour associated antigens recognised by cellular or humoral effectors of the immune system are potential targets for antigen specific cancer immunotherapy. Different categories of cancer antigens have been identified that induce cytotoxic T lymphocyte (CTL) responses in vitro and in vivo, namely: (1) "cancer testis" (CT) antigens, expressed in different tumours and normal testis, (2) melanocyte differentiation antigens, (3) point mutations of normal genes, (4) self antigens that are overexpressed in malignant tissues, and (5) viral antigens. Clinical studies with peptides and proteins derived from these antigens have been initiated to study the efficacy of inducing specific CTL responses in vivo. Immunological and clinical parameters for the assessment of antigen specific immune responses have been defined—delayed type hypersensitivity (DTH), CTL, autoimmmune, and tumour regression responses. Specific DTH and CTL responses and tumour regression have been observed after the intradermal administration of tumour associated peptides alone. Peptide specific immune reactions were enhanced after using granulocyte macrophage stimulating factor (GM-CSF) as a systemic adjuvant by increasing the frequency of dermal antigen presenting Langerhans cells. Complete tumour regression has been observed in the context of measurable peptide specific CTL. However, in single cases with disease progression after an initial tumour response, either a loss of single antigens targeted by CTL or of the presenting major histocompatibility complex (MHC) class I allele was detected, pointing towards immunisation induced immune escape. Cytokines to modulate antigen and MHC class I expression in vivo are being evaluated to prevent immunoselection. Recently, a new CT antigen, NY-ESO-1, has been identified on the basis of spontaneous antibody responses to tumour associated antigens. NY-ESO-1 appears to be one of the most immunogenic antigens known to date, with spontaneous immune responses observed in 50% of patients with NY-ESO-1 expressing cancers. Clinical studies have been initiated to evaluate the immunogenicity of different NY-ESO-1 constructs to induce both humoral and cellular immune responses in vivo.